Kontibusi Pendapatan Usahatani Padi Ladang Terhadap Pendapatan Petani Di Desa Taraudu Kecamatan Sahu Kabupaten Halmahera Barat - Nofrasilia Ngamon; Joachim N.K. Dumais; Sherly G. Jocom (AGRI-SOSIOEKONOMI, 2022)
The purpose of this study was to determine and calculate the contribution of upland rice farming income to farmers' income. This research was conducted from September 2021 to November 2021. Primary data were obtained directly from selected respondents at the research location. The sampling method was carried out with a sampling census which made all members of the population as samples, the population in this study was 40 field rice farmers in Taraudu Village. The analysis used in this study is analyzed using the contribution formula and is presented in tabular form. The results of the study showed that upland rice farming contributed 10.72% to farmers' income.